Hilirisasi Riset dan Inovasi Produk dalam Rangka Mendukung Program Makan Bergizi Gratis (MBG) di Lombok - Wahim, Isdar; Ahmadi, Lukman; Herman; Jumraidin; Muhtasom, Ali; Setiadji, Amirosa Ria; Aprianto, Yusup (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
The Free Nutritious Meal Program is a strategic government initiative aimed at improving the nutritional quality of students at the elementary, junior high, and senior high school levels while supporting the development of healthy and competitive human resources. This study aims to examine the implementation of the program in schools in Lombok, assess the suitability of menus with recommended nutritional standards, identify challenges at the school level, and formulate recommendations to enhance program quality and sustainability. A qualitative field study approach was employed using direct observation, in-depth interviews, and focus group discussions involving school representatives and meal program kitchen managers. The findings indicate that the program has generally followed balanced nutrition principles with support from nutrition experts; however, limitations remain in menu diversity, consistency of portion sizes across schools, and the utilization of local food resources, particularly fish-based protein sources. In addition, limited human resource capacity among kitchen managers affects menu innovation and food processing practices. These results suggest that strengthening the program requires improved kitchen management, greater integration of local food resources, and continuous capacity-building initiatives. The program has strong potential to serve as an effective instrument for enhancing students’ health and learning quality when supported by standardized and sustainable management systems.